2022
DOI: 10.3390/ma15103725
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Rapid Tooling in Rapid Heat Cycle Molding: A Review

Abstract: Rapid tooling (RT) and additive manufacturing (AM) are currently being used in several parts of industry, particularly in the development of new products. The demand for timely deliveries of low-cost products in a variety of geometrical patterns is continuing to increase year by year. Increased demand for low-cost materials and tooling, including RT, is driving the demand for plastic and rubber products, along with engineering and product manufacturers. The development of AM and RT technologies has led to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 136 publications
(215 reference statements)
0
15
0
Order By: Relevance
“…In addition, the appearance of the products significantly influences a consumer's choice 5 . Therefore, several studies have been conducted to improve the strength or appearance, reduce the weld line, and move it to a position where the tensile stresses are low 6–15 . Uyen et al 6 noted that the appearance of the weld line was influenced by the mold temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the appearance of the products significantly influences a consumer's choice 5 . Therefore, several studies have been conducted to improve the strength or appearance, reduce the weld line, and move it to a position where the tensile stresses are low 6–15 . Uyen et al 6 noted that the appearance of the weld line was influenced by the mold temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they indicated that the mold heating temperature affected the appearance during the rapid heating cycle molding process (RHCM). RHCM process is one of the method of improving strength and appearance of weld line 8,9 . Although, mold and melt temperature control is an effective method for improving weld lines, simply increasing the temperature causes other problems such as sink marks and deformation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RT is a natural extension of AM; it originated from the need to assess the performance of AM models. To enable performance validation, such models (prototypes) must be produced using the same material and production process used for full-scale production [5,6]. Today, the main application of RT in conventional production processes is in casting, where it is used in complex-shape and net-shape manufacturing [7,8].…”
Section: Introductionmentioning
confidence: 99%